2014
DOI: 10.1038/jid.2013.417
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Keratinocytes and T Cells in a 3D Microenvironment: A Model to Study Inflammatory Skin Diseases

Abstract: The interaction between keratinocytes and immune cells plays a major role in the development of inflammatory skin diseases like psoriasis and atopic dermatitis. Pharmacological intervention to inhibit T cell-derived proinflammatory mediators is an effective therapy in the treatment of psoriasis. Here, we present a model to study the interaction between keratinocytes and T cells in a three-dimensional (3D) microenvironment, based on human skin equivalents populated with CD4+ T cells. T cell migration into the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 46 publications
(52 reference statements)
4
99
0
Order By: Relevance
“…IL-8 and KC-like) by atopic keratinocytes that may perpetuate a proinflammatory state in the atopic skin. These data are in agreement with previous studies showing an active involvement of AMPs and keratinocytes in the pathogenesis and/or exacerbation of AD (1,2,(26)(27)(28)(29)(30)(31)(32)(33). In particular, keratinocyte-secreted AMPs serve as alarmins able to orchestrate the cutaneous immune response in AD (27,29).…”
Section: Discussionsupporting
confidence: 93%
“…IL-8 and KC-like) by atopic keratinocytes that may perpetuate a proinflammatory state in the atopic skin. These data are in agreement with previous studies showing an active involvement of AMPs and keratinocytes in the pathogenesis and/or exacerbation of AD (1,2,(26)(27)(28)(29)(30)(31)(32)(33). In particular, keratinocyte-secreted AMPs serve as alarmins able to orchestrate the cutaneous immune response in AD (27,29).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the CD4 þ T cells, like the CD8 þ T cells, show oligoclonal expansion in psoriatic skin 49,50 . Activated CD4 þ T cells have been shown to induce a psoriasiform inflammation in epidermal cells in a recently set up 3D model of inflammatory skin disease 51 . In the past, it has been shown that injection of pre-psoriatic skin with CD4 þ , and not CD8 þ T cells, induced psoriasis 52 .…”
Section: Discussionmentioning
confidence: 99%
“…2) and possible cross-talk events between keratinocytes and immune cells. Recent investigation of the interactions between keratinocytes and T cells in a three-dimensional microenvironment showed CD4+ T cell migration into the dermis, which initiated keratinocyte activation within 2 days [67]. The psoriasiform inflammation was also observed using Th1-polarized and Th17-polarized CD4+ T cells.…”
Section: Animal Models Of Ps and Psamentioning
confidence: 99%
“…The psoriasiform inflammation was also observed using Th1-polarized and Th17-polarized CD4+ T cells. Treatment with anti-inflammatory drugs reduced the expression of proinflammatory cytokines and chemokines, leading to the suppression of the psoriasiform inflammation [67]. In vitro keratinocyte coculture also allowed for the characterizing of the cross-talk of cytokines and growth factors, where periostin tuned the magnitude of keratinocyte proliferation and differentiation by interacting with the paracrine IL-1α/IL-6 loop [68].…”
Section: Animal Models Of Ps and Psamentioning
confidence: 99%